Nanosilica Extraction from Grumusol Soil - Fitri, Medya Ayunda; Syahriyah, Farikha Alfi; Azizah, Zahrotul (2477 - 6165, 2023)
Grumusol soil is a type of soil that contains significant amounts of silica. Silica content in grumusol soil can reach up to 90%. The aim of this research was to determine the characteristics of silica nanostructures in Grumusol soil. The stages of the research were carried out including the preparation of raw materials, silica extraction, and XRD analysis. The raw material preparation stage is carried out by cleaning the grumusol soil from dirt. The second stage was carried out by synthesizing silica with the base extraction method and followed by acid deposition. The final stage is X-Ray Diffracion (XRD) analysis. The results of the research that has been carried out is the FWHM value of 0.0900 (<0.1) which indicates that the crystals produced have very good crystals with a very regular structure. The crystal size which includes nanosilica is 39.5076-48.6633 nm for 3M NaOH with 1 and 3 hours extraction time and 5M NaOH with 1 hour extraction time